Экономика: учебник по курсу "Экономическая теория" / ред. А. С. Булатов - Булатов А. С. (БЕК, 1999)
Экземпляры: аб. (2000) / Инвентарный номер: 41863 / Сис.шифр: 65.01 / Авт.знак: Э40 / ГРНТИ: 06 / ББК: 65.01я7